KRISIS LINGKUNGAN DALAM PERSPEKTIF SPIRITUAL ECOLOGY - Supian Supian (Universitas Negeri Medan, 2018)
ABSTRACT The reality of the crisis and environmental degradation is a major problem that the world's population is facing today. Experts argue that the current crisis and environmental degradation are closely related to the mentality and misconceptions about the environment itself. Long debates and intense discussions, especially between science and religion, are intensively undertaken in an attempt to find a way out of the ongoing environmental degradation. Various perspectives arise and are expected, including from the spiritual ecology approach, to rethink the relationship between man and the earth, or on a wider scale, the relationship between man and the earth in the corridor of cosmic cosmic beliefs as his philosophical basis. The emergence of environmental crisis is caused by the concept of the relationship between humans and the natural environment is wrong. The problem of environmental damage is essentially a humanitarian problem that is closely related to the value system, customs and religion in human life. Therefore, the way to overcome it is not enough just to do business that is purely technical, but more importantly there must be a business that is educative and persuasive, that is with a philosophical understanding of the meaning of nature's existence in relation to God, man and nature, to change attitude and human behavior towards nature. Many even consider the need for a spiritual revolution to save nature and the environment, which is now at a spiritual stage of spirituality and then offers the application of the concept of eco-spirituality. ie to incorporate spiritual values in aspects of human environmental studies, where religion has a very dominant role. This paper delivers bluntly what are the causes of environmental damage in the spiritual ecology approach. Keywords: Spiritual Ecology, Environmental Crisis, teleology, the universe